An integrated temporary negative pressure assisted microfluidic chip for DNA isolation and digital PCR detection1. Issue 100 (29th October 2015) - Tian, Qingchang; Yu, Baodong; Mu, Ying; Xu, Yanan; Ma, Congcong; Zhang, Tao; Jin, Wei; Jin, Qinhan
<x xml:space="preserve">Abstract</x> An integrated DNA purification and digital PCR (dPCR) detection microfluidic chip was developed in this study.